Patient perspective on virtual prechemotherapy visits in gynecologic oncology - Monica J. Janke; Bryan Aaron; Hannah D. McLaughlin; Yang Liu; Shitanshu Uppal (Elsevier, 2024)
Objective: To assess gynecologic oncology patients' experiences with virtual prechemotherapy evaluation and determine preference for incorporating virtual visits into a chemotherapy schedule. Methods: From June-August 2023, a survey was distributed to patients with gynecologic malignancies who had both an in-person and virtual prechemotherapy visit at a tertiary comprehensive cancer center. Patient satisfaction and preference for incorporating virtual visits was elicited. Patients who preferred ≥ 50 % of prechemotherapy visits to be virtual were classified as "virtual-leaning" and those who preferred < 50 % virtual as "in-person-leaning." Results: Of 110 eligible patients, 93 agreed to participate and 73 completed the survey, yielding an overall 66.4% response rate and 78.5% (73/93) survey completion rate. Overall satisfaction with in-person and virtual visits were rated positively at similar rates (in-person 87.7%, virtual 87.2%). Sixty-four (88.4%) patients preferred some proportion of their visits to be virtual, 5 (7.0%) preferred no virtual care, and 4 (5.0%) had no preference. In a 6-cycle schedule of chemotherapy, the median number of preferred virtual visits was 3 (IQR 1.8-4.2). Forty-six (63.0%) patients were "virtual-leaning" and 23 (32.0%) were "in-person-leaning." When comparing groups, there was no difference in age, race, category of residence, commute, experience with technical difficulty, primary disease site, disease stage, number of prior chemotherapy cycles, or number of prior virtual visits. Conclusions: Most patients are highly satisfied with virtual visits and prefer virtual care to be included when undergoing chemotherapy. A hybrid model should be offered to gynecological cancer patients undergoing chemotherapy, with patient preference dictating the cadence of virtual visits.